2023
DOI: 10.1002/prca.202200081
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a potential prognostic plasma biomarker of acute ischemic stroke via untargeted LC‐MS metabolomics

Abstract: PurposeStroke is the sudden death of brain cells in a localized area due to an inadequate blood flow or blood vessel rupture, and it seriously affects the quality of life. The metabolite biomarkers are needed for predicting the functional outcome of acute ischemic stroke (AIS).Experimental DesignTo identify biomarkers for AIS, untargeted LC/MS metabolomics was performed on plasma samples from subjects with favorable prognosis (mRS ≤ 2) and unfavorable prognosis (mRS > 2). The identified markers were further… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Additionally, Wang’s research found that serum bile acids are a risk factor for poor prognosis after IS and a protective factor for the brain [ 122 , 125 ]. Furthermore, glycylcholic acid levels may be indicative of prognosis in IS patients, with higher levels potentially reflecting a better outcome [ 126 ]. The observed increase in glutamic acid and decrease in glutamine are believed to be associated with an increased risk of cardiovascular disease, particularly stroke [ 127 ].…”
Section: Identify Potential Biomarkers For Ismentioning
confidence: 99%
“…Additionally, Wang’s research found that serum bile acids are a risk factor for poor prognosis after IS and a protective factor for the brain [ 122 , 125 ]. Furthermore, glycylcholic acid levels may be indicative of prognosis in IS patients, with higher levels potentially reflecting a better outcome [ 126 ]. The observed increase in glutamic acid and decrease in glutamine are believed to be associated with an increased risk of cardiovascular disease, particularly stroke [ 127 ].…”
Section: Identify Potential Biomarkers For Ismentioning
confidence: 99%
“…The aim of the present study was to investigate changes in metabolite levels of fecal matter in male and female offspring exposed to FADD and ChDD during early neurodevelopment and an ischemic stroke during adulthood. Untargeted metabolite analysis has been shown to provide some insight to changes after stroke (Zhao et al, 2022), predict stroke outcome (Chi et al, 2021), as well as generate data for biomarkers (Li et al, 2018; M.-H. Wu et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that plasma succinate concentrations can be used as a biomarker for pre-hospital aortic disease diagnosis and reliable differentiation from acute myocardial infarction and pulmonary embolism when patients present with chest pain. Glycocholic acid has been identified as a potential plasma metabolite marker for the functional outcome after acute ischemic stroke (AIS) in an untargeted LC/MS metabolomics study ( Wu et al, 2023 ). Elevated levels of 4-hydroxyphenylacetic acid and decreased levels of threonine were found to be associated with an increased risk of cardiovascular events ( Ferreira-Divino et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%